Analisis Kompensasi Kepemimpinan Transformasional Terhadap kepuasan Kerja Karyawan Hotel Bintang Lima di Surakarta - Puput Melati; Agus Suyatno; Khabib Alia Akhmad (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Employee happiness at five-star hotels in Surakarta is the target of this research, which intends to examine the impact of transformational leadership pay on this variable. There are 98 people working at five-star hotels in the Surakarta region who make up the study's population. Pay, transformasional leadership, and contentment in one's work environment are the study factors. Questionnaires served as the main data source for this investigation. Data was analyzed with the help of SPSS 25. According to the findings, the two most important factors influencing an employee's level of work satisfaction are financial pay and transformational leadership.